The Effectiveness of Problem Based Learning Model Base on Open-Ended to Improve Mathematical Creative Thinking Skills - Baetul 'Iza; Hesti Khasanah (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Abstract: The ability to think mathematically creative students is very important in mathematics teaching. students' mathematical creative thinking ability is still relatively low can be seen from various factors. This study aims to find out how the implementation of Problem Based learning model based on open-ended to improve students' mathematical creative thinking skills, and to determine the effectiveness of open-ended based Problem Based learning model based on open-ended to improve students' mathematical creative thinking skills. This type of research is quantitative research with experimental methods. The population in this study were all grade VIII MTs N 1 Purbalingga students. The sample of this research is students of grades VIII G and VIII H with sampling techniques using Convenience Sampling. The instruments used in this study were pretest and posstes description questions with data analysis using the T-test. Based on the research that has been done, it can be concluded that the implementation of the based learning model based on open-ended is done very well, with an observer score of 3.46. From the results of data analysis, namely the T-test, it can be seen that the based problem-based learning model based on open-ended is effective for improving students' mathematical creative thinking skills, it can be seen from the significance value of 0.006 < 0.05, then H0 is rejected and H1 is accepted, which means that the problem based learning model based on open-ended effective to improve students' mathematical creative thinking skills